Impactos da realocação compulsória de ribeirinhos para o Reassentamento Urbano Coletivo (RUC) Água Azul com a implementação da Usina Hidrelétrica Belo Monte em Altamira - Pará 2014/2015 - CORREA, Raimundo Nonato Pires (2023)
This paper approaches the impacts caused by the compulsory relocation of riverside dwellers to the Água Azul Collective Urban Resettlement (RUC) with the construction of the Belo Monte Hydroelectric Power Plant in Altamira - Pará. In this way, his historiography aims to contribute to the understanding of the impacts of this process on the way of life of traditional communities that were violently displaced by the Belo Monte Consortium, consortium of companies responsible for the viability of the work. Thus, the concepts of "Impacted by Dams" and "Large Projects" were worked on, whose methodology was focused on a bibliographical research and interviews with riverside families from the Collective Urban Resettlement (RUC) Água Azul, addressing the context of the relocation period and the current context of the event in question. Taking as a hypothesis the perspective that the economic, social and cultural impacts that affected these communities and the lack of compliance with the conditions imposed by the Brazilian Institute of Environment (IBAMA) and other environmental agencies were not taken into account in the construction project as ICMBIO for the start-up, completion and operation of the Plant. Thus, we sought to understand how these riverside people were impacted in their way of life, their traditions, and above all, in their dignity and rights when they were forced to withdraw, even violently, from their territories with promises that were never fulfilled. fulfilled by Norte Energia.